Process evaluation of implementation fidelity in a Danish health-promoting school intervention - Ane Høstgaard Bonde; Nanna Wurr Stjernqvist; Marianne S. Sabinsky; Helle Terkildsen Maindal (BMC, 2018)
Abstract Background "We Act" is a health-promoting school intervention comprising an educational, a parental and a school component. The intervention was implemented in 4 Danish public schools with 4 control schools. The objectives were to improve pupils' dietary habits, physical activity, well-being and social capital using the Investigation, Vision, Action & Change (IVAC) health educational methodology. The target group was pupils in grades 5-6. The purpose of this study was to evaluate implementation fidelity and interacting context factors in the intervention schools. Methods The Medical Research Council's new guidance for process evaluation was used as a framework. Data were collected concurrently and evenly at the 4 intervention schools through field visits (n = 43 days), questionnaires (n = 17 teachers, 52 parents), and interviews (n = 9 teachers, 4 principals, 52 pupils). The data were analysed separately and via triangulation. Results A total of 289 pupils participated, and 22 teachers delivered the educational component in 12 classes. In all schools, the implementation fidelity to the educational methodology was high for the Investigation and Vision phases as the teachers delivered the proposed lessons and activities. However, the implementation fidelity to the Action & Change phase was low, and little change occurred in the schools. The pupils' presentation of their visions did not work as intended as an impact mechanism to prompt actions. The implementation of the parental and the school components was weak. The main context factors influencing implementation fidelity were a poor fit into the school-year plan and weak management support. Conclusions Although 'We Act' was designed to comply with evidence- and theory-based requirements, IVAC and the health-promoting school approach did not result in change. The time dedicated to schools' preparation and competence development may have been too low. This must be considered in future process evaluation research on health-promoting schools and by school health promotion administrators when planning future school interventions. Trial registration ISRCTN85203017